Practicing Ihsan with Tasawuf Amaliyah - Fuad, Ahmad Masfuful (Al-Albab, 2018)
Moch. Djamaluddin Ahmad, Tasawuf Amaliyah, Jombang: Februari, 2018Practicing Ihsan with Tasawuf AmaliyahAs Islam is spread out by the Prophet of Muhammad (Peace be Upon Him: PbUH) for the seeks of becoming the blessing for the universe (raḥmatan lil ‘ālamīn), Islam offers three main pillars namely iman, islam, and ihsan. The first pillar of iman consisting of its principles (rukun) is the manifestation of the belief of a believer which is known as theology (akidah). The second pillar of Islam together with its five principles is the manifestation of the practice of Islamic teaching (syariat). And the third pillar of ikhsan is the essence of the practicing of the values of Allah the almighty God and the values of the worshipers as later known as hakikat.